Effects of dapagliflozin on development and progression of kidney disease in patients with type 2 diabetes: an analysis from the DECLARE–TIMI 58 randomised trial. Issue 8 (August 2019) - Mosenzon, Ofri; Wiviott, Stephen D; Cahn, Avivit; Rozenberg, Aliza; Yanuv, Ilan; Goodrich, Erica L; Murphy, Sabina A; Heerspink, Hiddo J L; Zelniker, Thomas A; Dwyer, Jamie P; Bhatt, Deepak L; Leiter, Lawrence A; et al.
Summary: Background: Sodium-glucose co-transporter-2 (SGLT2) inhibitors have shown beneficial effects on renal outcomes mainly in patients with established atherosclerotic cardiovascular disease. Here we report analyses of renal outcomes with the SGLT2 inhibitor dapagliflozin in the DECLARE–TIMI 58 cardiovascular outcomes trial, which included patients with type 2 diabetes both with and without established atherosclerotic cardiovascular disease and mostly with preserved renal function. Methods: In DECLARE–TIMI 58, patients with type 2 diabetes, HbA1c 6·5–12·0% (47·5–113·1 mmol/mol), with either established atherosclerotic cardiovascular disease or multiple risk factors, and creatinine clearance of at least 60 mL/min were randomly assigned (1:1) to 10 mg dapagliflozin or placebo once daily. A prespecified secondary cardiorenal composite outcome was defined as a sustained decline of at least 40% in estimated glomerular filtration rate [eGFR] to less than 60 mL/min per 1·73m 2, end-stage renal disease (defined as dialysis for at least 90 days, kidney transplantation, or confirmed sustained eGFR <15mL/min per 1·73 m 2 ), or death from renal or cardiovascular causes; a prespecified renal-specific composite outcome was the same but excluding death from cardiovascular causes. In this renal analysis, we report findings for the components of these composite outcomes, subgroup analysis of these composite outcomes, and changes in eGFR at different timepoints. DECLARE–TIMI 58 is registered withClinicalTrials.gov, numberNCT01730534 . Findings: The trial took place between April 25, 2013, and Sept 18, 2018; median follow-up was 4·2 years (IQR 3·9–4·4). Of the 17 160 participants who were randomly assigned, 8162 (47·6%) had an eGFR of at least 90 mL/min per 1·73 m 2, 7732 (45·1%) had an eGFR of 60 to less than 90 mL/min per 1·73 m 2, and 1265 (7·4%) had an eGFR of less than 60 mL/min per 1·73 m 2 at baseline (one participant had missing data for eGFR); 6974 (40·6%) had established atherosclerotic cardiovascular disease and 10 186 (59·4%) had multiple risk factors. As previously reported, the cardiorenal secondary composite outcome was significantly reduced with dapagliflozin versus placebo (hazard ratio [HR] 0·76, 95% CI 0·67–0.87; p<0·0001); excluding death from cardiovascular causes, the HR for the renal-specific outcome was 0·53 (0·43–0·66; p<0·0001). We identified a 46% reduction in sustained decline in eGFR by at least 40% to less than 60 mL/min per 1·73 m 2 (120 [1·4% vs 221 [2·6%]; HR 0·54 [95% CI 0·43–0·67]; p<0·0001). The risk of end-stage renal disease or renal death was lower in the dapagliflozin group than in the placebo group (11 [0·1%] vs 27 [0·3%]; HR 0·41 [95% CI 0·20–0·82]; p=0·012). Both the cardiorenal and renal-specific composite outcomes were improved with dapagliflozin versus placebo across various prespecified subgroups, including those defined by baseline eGFR (cardiorenal outcome pinteraction =0·97; renal-specific outcome pinteraction =0·87) and the presence or absence of established atherosclerotic cardiovascular disease (cardiorenal outcome pinteraction =0·67; renal-specific outcome pinteraction =0·72). 6 months after randomisation, the mean decrease in eGFR was larger in the dapagliflozin group than in the placebo group. The mean change equalised by 2 years, and at 3 and 4 years the mean decrease in eGFR was less with dapagliflozin than with placebo. Interpretation: Dapagliflozin seemed to prevent and reduce progression of kidney disease compared with placebo in this large and diverse population of patients with type 2 diabetes with and without established atherosclerotic cardiovascular disease, most of whom had preserved renal function. Funding: AstraZeneca.